Central Banks Use of Derivatives and Other Contingent Liabilities : Analytical Issues and Policy Implications - Schumacher, Liliana (IMF Working Papers; Working Paper, 2000)
Whereas some central bank derivatives and other contingent liabilities arise from anomalous circumstances, there are a number of positive reasons that explain their popularity. After analyzing the rationale for these operations, we stress that most of these operations, being off-balance sheet, increase the risk and reduce the transparency of central bank accounts. This in turn makes more difficult the assessment of the financial position of the monetary authority and, by implication, of the macroeconomic conditions of the country. To deal with this issue, we suggest a comprehensive portfolio approach that values, in an economic sense, all assets and liabilities of the central bank.